Emotion Regulation as the Role Moderator of Self-Esteem on Adolescents Fear of Missing Out - Alawi Mahmud; Elis Anisah Fitriah; Witrin Gamayanti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
Fear of missing out (FoMO) is derived from the anxiety that arises when an individual feels excluded from informational and experiential aspects due to exposure to social media. Therefore, this study aimed to determine the contribution of emotion regulation as a moderator on the role of self-esteem on adolescents fear of missing out. A quantitative method employing a causality design was employed, involving 349 active social media users aged 15 to 18. The measurement tools used consisted of psychological scales, namely fear of missing out, two-dimensional self-esteem, and emotion regulation questionnaire. Furthermore, the data analysis was conducted using Moderated Regression Analysis (MRA), which reported a significant impact of self-esteem on fear of missing out, with emotion regulation acting as a moderator. The result showed the significance of adolescents possessing positive self-esteem coupled with adaptive emotion regulation to mitigate the inclination towards experiencing fear of missing out while using social media.